1961
DOI: 10.1136/hrt.23.1.66
|View full text |Cite
|
Sign up to set email alerts
|

A Current Concept of the Regulation of Blood Volume

Abstract: To the unspecialized reader concerned with management of the aedema of disease, the rapid accumulation of proven influences on the renal regulation of extracellular electrolyte content and fluid volume may pose a problem in integration. This presentation does not constitute a comprehensive review (Smith, 1957;Grossman, 1957) but rather a summary of present understanding of a homeostatic mechanism, the existence of which is receiving tentative acceptance. This mechanism appears to operate primarily by correctin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1963
1963
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Unfortunately, the present study has failed to demonstrate any value in the hzmatocrit as a means of prediction of total blood volume. There is, of course, a significant correlation between red-cell volume and hzmatocrit, but total blood volume is the more important determinant of circulatory tolerance to hzmorrhage (Reeve and Vincent, 1962;Pearce, 1961;Hercus et a%, 1961). It has been pointed out already, but should be emphasized, that the mean venous hzmatocrit is identical in the groups with and without malignant disease.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the present study has failed to demonstrate any value in the hzmatocrit as a means of prediction of total blood volume. There is, of course, a significant correlation between red-cell volume and hzmatocrit, but total blood volume is the more important determinant of circulatory tolerance to hzmorrhage (Reeve and Vincent, 1962;Pearce, 1961;Hercus et a%, 1961). It has been pointed out already, but should be emphasized, that the mean venous hzmatocrit is identical in the groups with and without malignant disease.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in plasma volume with spinal anaesthesia would depend on the degree to which blood volume regulating factors were influenced, and the degree of compensation provided by the vasopressor. Since the volume regulating mechanisms 21,22 are as yet imperfectly understood, no attempt can be made to speculate on how they would be affected by this method of anaesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…Henry and Pearce (1956) concluded that when the left atrium is distended, stretch receptors send messages to the hypothalamus that result in inhibition of the antidiuretic hormone and lead to a water diuresis; and Pearce (1961) has summarized this work in discussing the regulation of the blood volume. I was at first hesitant to accept the suggestion that this mechanism might explain the diuresis of the paroxysmal arrhythmias for the three following reasons.…”
Section: Studies In Attacksmentioning
confidence: 99%